Annual malignant transformation rate of oral leukoplakia remains consistent: A long-term follow-up study. (November 2020) - Evren, Ilkay; Brouns, Elisabeth R.; Wils, Leon J.; Poell, Jos B.; Peeters, Carel F.W.; Brakenhoff, Ruud H.; Bloemena, Elisabeth; de Visscher, Jan G.A.M.
Highlights: Annual malignant transformation rate of oral leukoplakia remains consistent during long-time follow-up. Regular long-term or even life-long follow-up of oral leukoplakia is advocated. Oral leukoplakia on specific subsites (tongue and floor of mouth), have a high risk of malignant transformation. Differentiated dysplasia is as common as classic dysplasia in oral leukoplakia. Presence of epithelial dysplasia in oral leukoplakia is associated with malignant transformation. Abstract: Objectives: Numerous clinical and histopathological characteristics have been associated with malignant transformation (MT) of oral leukoplakia (OL), including classic and differentiated epithelial dysplasia, but MT predictions remain suboptimal. The objective of this study was to determine the annual MT rate of OL and to identify clinicopathological risk factors associated with MT. Patients and methods: 170 patients with OL were included in this retrospective cohort study, 117 females and 53 males. Follow-up ranged from 12 to 219 months (median 54). The analyzed variables included age, gender, smoking habits, clinical presentation, subsite, size and treatment. In a subgroup of 140 patients, histopathological diagnoses were reviewed with regard to the presence of dysplasia, discerning both classic dysplasia and differentiated dysplasia. Results: MT occurred in 23% of the patients, resulting in an annual MT rate of 4.9% (95% CI: 3.5 – 6.6) which remained consistent. High-risk subsite (tongue and floor of mouth) was the only clinical predictor for MT (Hazard Ratio = 2.7, 95% CI: 1.3 – 5.5, p  = 0.007). In 140 patients, classic dysplasia (Hazard Ratio = 7.2, 95% CI: 1.6 – 33.1, p  = 0.012) and differentiated dysplasia (Hazard Ratio = 6.6, 95% CI: 1.2 – 25.4, p  = 0.026) were predictors for MT. Binary grading between dysplasia and no dysplasia was significant for predicting MT (Hazard Ratio = 6.4, 95% CI: 1.5 – 27.5, p  = 0.013). Conclusion: Since annual MT rate of OL remains stable during follow-up, regular long-term or even life-long follow-up is advocated. Specific oral subsites and epithelial dysplasia are predictors for MT of OL.